Evaluation of estrogen receptor alpha and beta and progesterone receptor expression and correlation with clinicopathologic factors and proliferative marker Ki-67 in breast cancers - Rosa, Fabiola E. [UNESP]; Caldeira, Jose R. F. [UNESP]; Felipes, Joice; Bertonha, Fernanda B. [UNESP]; Quevedo, Francisco C.; Domingues, Maria Aparecida Custódio [UNESP]; Moraes, Francisco A.; Rogatto, Silvia Regina [UNESP] (W B Saunders Co-elsevier Inc, 2008)
To elucidate the molecular profile of hormonal steroid receptor status, we analyzed ER-alpha, ER-beta, and PGR mRNA and protein expression in 80 breast carcinomas using reverse transcriptase polymerase chain reaction (RT-PCR), quantitative RT-PCR, and immunohistochemical analysis. Qualitative analysis revealed positive expression of ER-alpha, ER-beta, and PGR mRNA in 48%, 59%, and 48% of the breast carcinomas, respectively. ER-alpha, ER-beta, and PGR transcript overexpression was observed in 51%, 0%, and 12% of the cases, respectively, whereas moderate or strong protein expression was detected in 68%, 78%, and 49% of the cases, respectively. Tumor grade was negatively correlated with transcript and protein levels of ER-alpha (P = .0169 and P = .0006, respectively) and PGR (P = .0034 and P = .0005, respectively). Similarly, proliferative index Ki-67 was negatively associated with transcript and protein levels of ER-alpha (P = .0006 and P < .0001, respectively) and PGR (P = .0258 and P =. 0005, respectively). These findings suggest that ER-alpha and PGR expression are associated with well-differentiated breast tumors and less directly related to cell proliferation. A significant statistical difference was observed between lymph node status and ER-beta protein expression (P = .0208). In ER-alpha-negative tumors, we detected a correlation between ER-beta protein expression and high levels of Ki-67. These data suggest that ER-beta could be a prognostic marker in human breast cancer. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: breast cancer; estrogen receptor; progesterone receptor; mRNA expression; immunohistochemistry